Burn Wound Healing Activity Of Ethanol Extract Gel Of Guava Peel (Psidium Guajava Linn.) In Rabbits (Oryctolagus Cuniculus). - mohammad firdaus alshol; Mujtahid Bin Abdul Kadir; Datin An Nisa Sukmawati; Prayoga Fery Yuniarto; Herman Herman (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Traditional medicine using natural ingredients such as plants is becoming increasingly popular. Guava is a herbal plant used to treat various ailments, including burns. This study aims to evaluate the effectiveness of guava (Psidium guajava Linn.) peel extract gel in healing second-degree burns in rabbits (Oryctolagus cuniculus) and to determine the optimal dosage. This study used maceration and phytochemical screening methods, which identified alkaloids, triterpenoids, steroids, saponins, flavonoids, and tannins. Burns were induced using a hot metal on the rabbit's back. Twenty-five male rabbits weighing 1.5–2.5 kg were randomly divided into five groups (n = 5 per group). The experimental design was a Completely Randomized Design (CRD) consisting of a positive control (Bioplacenton gel), a negative control (no treatment), and guava peel extract gel at concentrations of 3%, 5%, and 7%. CRD ensured that each treatment was assigned randomly to minimize experimental bias. Burn wound diameter was measured periodically throughout the treatment period. Data were analyzed using one-way ANOVA followed by the LSD test. The results showed a significant difference between treatments (p = 0.000). 7% guava peel extract gel was the most effective treatment, showing the greatest reduction in burn diameter with an average reduction of 9.08 mm. These findings suggest that guava peel extract gel has potential as an alternative therapy for burn wound healing.